Presumption of insolvency under law no. 37/2004: a call for reform to safeguard debtor welfare and social justice - Hamonangan S, Uli Ingot (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The Presumption of Insolvency doctrine in Article 2 paragraph (1) of Law No. 37/2004 allows debtors to be declared bankrupt if proven to have two creditors and one due debt, without verifying their actual insolvency. Recent data highlights its urgency: the SIPP system recorded 652 PKPU petitions and 94 bankruptcies in 2023, rising from 572 PKPU and 105 bankruptcies in 2022, while PKPU registrations surged from 199 cases in 2016 to 560 in 2023. Such growth indicates increasing reliance on bankruptcy and restructuring mechanisms, particularly affecting small and medium-sized debtors. This study applies a normative legal method with qualitative analysis of 201 court decisions issued between 2010 and 2023. The findings reveal three core issues: (1) procedural inequality from the reverse burden of proof, which disadvantages debtors, (2) socio-economic consequences including the loss of assets, employment, and reputation, and (3) remedial imbalance as the PKPU mechanism often arrives too late. Reform recommendations include establishing differential debt thresholds, introducing a grace period before bankruptcy, requiring social-impact assessments, and strengthening PKPU as the primary restructuring route. These measures are expected to balance creditor certainty with debtor protection while making social justice outcomes measurable through indicators such as recovery rates and access to legal remedies.